2013
DOI: 10.7869/tg.2012.106
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and management of gallbladder remnant after partial cholecystectomy

Abstract: Background: Partial cholecystectomy is usually performed with the aim of preventing bile duct injury and/or vascular injuries in situations where there is difficulty in performing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…This outcome may be attributed to an intact cystic duct with potential to drain into the gallbladder remnant, which likely serves as a reservoir for bile stasis, stone formation, and recurrent symptoms. 29 Incomplete evacuation of gallbladder contents at the time of subtotal cholecystectomy could also contribute to the observed recurrence of symptoms necessitating completion cholecystectomy. Interestingly, we observed that only patients in the laparoscopic subtotal cholecystectomy cohort underwent reoperation to remove the gallbladder remnant, whereas those that underwent a converted or planned open operation required no such intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome may be attributed to an intact cystic duct with potential to drain into the gallbladder remnant, which likely serves as a reservoir for bile stasis, stone formation, and recurrent symptoms. 29 Incomplete evacuation of gallbladder contents at the time of subtotal cholecystectomy could also contribute to the observed recurrence of symptoms necessitating completion cholecystectomy. Interestingly, we observed that only patients in the laparoscopic subtotal cholecystectomy cohort underwent reoperation to remove the gallbladder remnant, whereas those that underwent a converted or planned open operation required no such intervention.…”
Section: Discussionmentioning
confidence: 99%
“…These series include 3 to 11 patients with time spans ranging from 3 to 9 years. It has been shown both, in our series and the literature that patients present over a highly variable and wide‐ranging amount of time after initial cholecystectomy (range 1 month to 40 years) . CT, MRCP, ultrasound, and ERCP were used most often for diagnosis, with MRCP being the only modality used in all studies.…”
Section: Discussionmentioning
confidence: 79%
“…Only 5% of all elective laparoscopic cholecystectomies are converted to open, typically due to inflammation and adhesions impairing safe dissection . This inflammatory environment predisposes the patient to having, intentionally or unintentionally, a gallbladder remnant left behind . In our series, 11 patients had a laparoscopic converted to open cholecystectomy at the initial surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most important cause of remnant gallbladder is the remaining gallbladder tissue in the partial cholecys-tectomy surgery due to poor visualization of the anatomy of the cystic duct and gallbladder junction for reasons such as hemorrhage, adhesion, or inflammation. Partial cholecystectomy is more common in cholecystectomy which is performed after acute cholecystitis [3,4].…”
mentioning
confidence: 99%